Denitrification Is the Main Nitrous Oxide Source Process in Grassland Soils According to Quasi‐Continuous Isotopocule Analysis and Biogeochemical Modeling. Issue 6 (8th June 2020) - Ibraim, Erkan; Denk, Tobias; Wolf, Benjamin; Barthel, Matti; Gasche, Rainer; Wanek, Wolfgang; Zhang, Shasha; Kiese, Ralf; Butterbach‐Bahl, Klaus; Eggleston, Sarah; Emmenegger, Lukas; Six, Johan; et al.
Abstract: Isotopic composition of soil‐emitted nitrous oxide (N2 O), especially the intramolecular distribution of 15 N in N2 O known as site preference (SP), can be used to track the two major N2 O emitting soil‐processes nitrification and denitrification. Online analysis of SP in ambient air has been achieved recently, yet those approaches only allowed addressing large areas (footprints) on the basis of strong changes in surface atmospheric N2 O concentrations. Here, we combined laser spectroscopy with automated static flux chambers to measure, for the first time, SP of low N2 O fluxes with high sensitivity and temporal resolution and to explore its spatial variability. The measurements were then used to test the N2 O isotope module SIMONE in combination with the biogeochemical model LandscapeDNDC to identify N2 O source processes. End‐member mixing analysis of the data revealed denitrification as the predominant N2 O source. This finding was independent of the soil water content close to the soil surface, suggesting that N2 O production in the subsoil under high water‐filled pore space conditions outweighed the potential production of N2 O by nitrification closer to the surface. Applying the SIMONE‐LandscapeDNDC model framework to our field site showed that the modeled SP was on average 4.2‰ lower than the observed values. This indicates that the model parameterization reflects the dominant N2 O production pathways but overestimates the contribution of denitrification by 6%. Applying the stable isotope‐based model framework at other sites and comparing with other models will help identifying model shortcomings and improve our capability to support N2 O mitigation from agricultural ecosystems. Plain Language Summary: Between August and December 2017 the concentration and isotopic composition of soil emitted nitrous oxide (N2 O) was measured above a grassland site in Central Switzerland. Automated flux chambers were coupled to a custom‐built preconcentration and laser spectroscopy‐based online measurement method. The obtained results were used to validate a recently developed isotope submodule (SIMONE) for a biogeochemical model (LandscapeDNDC), to simulate fluxes of trace gases. Our results show a clear predominance of denitrification as the primary N2 O emitting source process. In contrast to previous studies, this dominance led to stable N2 O site preference values throughout the measurement campaign, a feature that was also represented by SIMONE. These findings will bridge current shortcomings in our model understanding and thereby help developing targeted N2 O mitigation strategies. Key Points: Spatial allocation and high instrumental sensitivity was achieved by combining automated flux chambers and laser spectroscopy with preconcentration We report on the first quasi‐continuous analysis of the intramolecular 15 N distribution (known as site preference, SP ) of soil‐emitted N2 O over a 3 months period Measurements and biogeochemical modeling revealed that denitrification was the dominant N2 O production pathway in the managed grassland